Spectroscopic Studies on TiO2 Nanoparticles-Bovine Serum Albumin Interaction Under Visible Light and Dark Conditions - Rajeshwari, A.; Amrita, Kumari; Chandrasekaran, N.; Mukherjee, Amitava (Asian Journal of Chemistry, 2015)
Titania (TiO2) nanoparticles are increasingly used in the consumer and industrial applications, but there is only a handful of studies regarding their interactions with protein molecules. The aim of the present study was to explore the interaction between TiO2 nanoparticles and bovine serum albumin (BSA) under visible light and dark conditions. The UV-visible spectral studies showed a concentration dependent increase in absorption intensity under both the conditions denoting the formation of BSA-TiO2 complex. The fluorescence quenching was noted upon addition of nanoparticles. The number of TiO2 binding sites on bovine serum albumin were determined (light: 0.6, dark: 1.9) by Stern-Volmer plot. The circular dichroism analysis showed significant changes in a-helix content of the protein structure upon adding TiO2. A significant reduction in reactive oxygen species generation by the TiO2 nanoparticles was observed upon interaction with bovine serum albumin for both the conditions denoting the protein modulated decrease in photo reactivity of TiO2 nanoparticles. This is one of the foremost studies to present a comparative estimation of the spectral changes upon interaction of bovine serum albumin with TiO2 nanoparticles under visible light and dark conditions. In a direct implication to potential cytotoxicity of TiO2 nanoparticles, this study confirms that interactions with bovine serum albumin can substantially reduce reactive oxygen species generation by the nanoparticles.